ANALISIS PENGARUH CURRENT RATIO DAN WORKING CAPITAL TURN OVER TERHADAP NET PROFIT MARGIN - Adwimurti, Yudhistira; Lumbantobing, Sabar Pardamean; Selfiani, Selfiani (Unversitas Prof. Dr. Moestopo (Beragama), 2023)
This research examines the influence of Current Ratio and Working Capital Turnover on Net Profit Margin in the Banking Sector listed on the Stock Exchange during the period 2015-2020. The aim of this study is to determine the extent of the influence of Current Ratio and Working Capital Turnover on Net Profit Margin in the Banking Sector listed on the Stock Exchange. This thesis uses the population of banking sector companies listed on the Indonesia Stock Exchange. The sample selected consists of banking sector companies listed in books 1 to 4. The data analysis techniques employed include Normality Test, Heteroskedasticity Test, and Multicollinearity Test. The hypothesis tests used are Simple Regression Test, T-Test, Significance Test, Correlation Test, Coefficient of Determination Test, Multiple Linear Regression Test, and Anova Test. The research results indicate that Current Ratio has a positive and significant influence on Net Profit Margin, meaning that a one-unit increase in the Current Ratio variable will increase Net Profit Margin. Working Capital Turnover also has a positive and significant influence on Net Profit Margin, meaning that a one-unit increase in the Working Capital Turnover variable will increase Net Profit Margin. Current Ratio and Working Capital Turnover together have a positive and significant influence on Net Profit Margin, meaning that a one-unit increase in both Current Ratio and Working Capital Turnover variables will increase Net Profit Margin.